1996
DOI: 10.2134/agronj1996.00021962008800050021x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield is Equal in Conventional, Reduced, and No Tillage after 20 Years

Abstract: Reduced tillage has increased dramatically over the past several years and is expected to continue to increase in the future. Continuous no‐till may become a popular tillage system with growers to facilitate compliance with government programs to control soil erosion. The objective of this research was to evaluate the long‐term effects of four tillage systems and five fertilizer regimes on corn (Zea mays L.) yield. A 20‐yr continuous‐corn tillage ✕ fertility study was conducted from 1970 to 1990 on an Ebbert s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 24 publications
(36 reference statements)
9
35
1
1
Order By: Relevance
“…At the beginning of the experiment, reduced tillage practices often resulted in smaller yields than the control, but this was not true for all years. These results are similar to results of Kapusta et al (1996) Weighted mean differences (t ha -1 ) (2005) reported that after 11 years, maize yields were not affected by tillage and residue practices but climate-related differences seemed to have a greater influence on the variation in yields. When residues were completely removed, yield reductions for maize were attributed to decreased soil water storage and excessive surface soil temperatures, especially in climates where conditions of moisture stress occurred during the growing season (Doran et al 1984).…”
Section: Reduced Tillage Continuous Maizesupporting
confidence: 89%
See 1 more Smart Citation
“…At the beginning of the experiment, reduced tillage practices often resulted in smaller yields than the control, but this was not true for all years. These results are similar to results of Kapusta et al (1996) Weighted mean differences (t ha -1 ) (2005) reported that after 11 years, maize yields were not affected by tillage and residue practices but climate-related differences seemed to have a greater influence on the variation in yields. When residues were completely removed, yield reductions for maize were attributed to decreased soil water storage and excessive surface soil temperatures, especially in climates where conditions of moisture stress occurred during the growing season (Doran et al 1984).…”
Section: Reduced Tillage Continuous Maizesupporting
confidence: 89%
“…Low yields in poorly drained soils are attributed to allelopathy (Yakle and Cruse 1984) and plant pathogens (Tiarks 1977). Kapusta et al (1996) reported that continuous maize production under no-tillage is most successful on well-drained soil, rather than on either imperfectly or poorly drained soil, especially under wet soil conditions. It has also been suggested that maize monocropping has drastic adverse effects on soil quality and crop yield especially under conditions of low traffic and no-tillage with mulching (Lal 1997).…”
Section: Effect Of Soil Texturementioning
confidence: 99%
“…Corn plant height is influenced by the water content in the soil (Hussain et al, 1999) [137], soil texture [138], the rate of fertilizer application [106,108,139] and cultivation methods [138]. Measurement of plant height can be conducted using high-resolution ultrasound distance sensing of the crop canopy [140,141].…”
Section: Use Of Sensors and Ndvimentioning
confidence: 99%
“…Corn produces taller plants at high plant population (Jonathan, et al, 2006). Soil moisture availability (Hussain et al, 1999), soil compaction, surface soil structure, and soil aggregation (Kladivko et al, 1986), fertilizer applications (Kapusta et al, 1996), and tillage system (Kladivko et al, 1986) also influence plant height of corn. In addition, plant height differs among corn cultivars (Rhoads and Stanley, 1973).…”
Section: Introductionmentioning
confidence: 99%